Effect of proximal translation of the osteotomized tibial tuberosity during tibial tuberosity advancement on patellar position and patellar ligament angle. Issue 1 (December 2016) - Neville-Towle, Jack; Makara, Mariano; Johnson, Kenneth; Voss, Katja
Abstract Background Cranial cruciate ligament insufficiency is a common orthopaedic problem in canine patients. This cadaveric and radiographic study was performed with the aim of determining the effect of proximal translation of the tibial tuberosity during tibial tuberosity advancement (TTA) on patellar position (PP) and patellar ligament angle (PLA). Results Disarticulated left hind limb specimens harvested from medium to large breed canine cadavers (n  = 6) were used for this study. Limbs were mounted to Plexiglass sheets with the stifle joint fixed in 135° of extension. The quadriceps mechanism was mimicked using an elastic band. Medio-lateral radiographs were obtained pre-osteotomy, after performing TTA without proximal translation of the tibial tuberosity, and after proximal translation of the tibial tuberosity by 3mm and 6mm. Radiographs were blinded to the observer for distance of tibial tuberosity proximalization following radiograph acquisition. Three independent observers recorded PP and PLA (tibial plateau method and common tangent method). Comparisons were made between the stages of proximalization using repeated measures ANOVA. Patellar position was found to be significantly more distal than pre-osteotomy, if the tibial tuberosity was not translated proximally (P  = 0.001) and if it was translated proximally by 3mm (P  = 0.005). The difference between pre-osteotomy PP and 6mm proximalization was not significant. The PLA was significantly larger if the tibial tuberosity was not translated proximally compared to tibial tuberosity proximalization of 6mm using the tibial plateau and the common tangent methods (P  = 0.006 andP  = 0.015 respectively). Conclusions Proximalizing the tibial tuberosity during TTA helps in maintaining vertical position of the patella in the patellar groove. Proximalization of the tibial tuberosity reduces PLA when compared to TTA without tibial tuberosity proximalization.